The early effects of uninephrectomy on rat kidney metabolic state using optical imaging. Issue 9 (23rd June 2020) - Mehrvar, Shima; Foomani, Farnaz H.; Shimada, Satoshi; Yang, Chun; Zheleznova, Nadezhda N.; Mostaghimi, Soudeh; Cowley, Allen W.; Ranji, Mahsa
Abstract: Uninephrectomy (UNX) is known to result in structural and metabolic changes to the remaining kidney, although it is uncertain if this alters the mitochondrial redox state and how soon such changes may occur. A custom‐designed fluorescence cryo‐imaging technique was used to quantitatively assess the effect of UNX by measuring the levels of nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD) in the remaining kidney. Kidneys were snap‐frozen 3 days following UNX, and the intrinsic fluorescence of NADH and FAD were optically acquired. The 3D images were created to characterize the NADH/FAD redox ratios (RR) of the right kidneys, which underwent UNX and the remaining kidneys 3 days following UNX. Both the NADPH‐oxidases (Nox2 and Nox4) and the mitochondria are the main sources of reactive oxygen species (ROS) production in tubular epithelial cells. Responses to the UNX were obtained in kidneys of normal Sprague Dawley (SD) rats, Dahl salt‐sensitive (SS) rats and SS rats in which NADPH‐oxidase isoform 4 (Nox4) was knocked out (SS Nox4−/− ). The results found that each of the strains exhibited similar increase in kidney weights averaging 17% after 3 days of UNX. SD and SS Nox4−/− rats both exhibited global reductions of the RR ( P < .05) with a similar tendency observed in SS rats ( P < .08), indicating increased ROS production. The unexpected reduction of the RR in the remnant kidneys of SS Nox4−/− rats indicates that mechanisms independent of H2 O2 produced from Nox4 may be responsible for this global increase of ROS. We propose that the reduced RR was largely a consequence of enhanced mitochondrial bioenergetics due to increased tubular workload of the remaining kidney. The data indicate that mitochondria become the dominant source of increased ROS following UNX and could represent an important hypertrophic signaling mechanism. Abstract : The mechanisms that signal the functional hypertrophic responses of the remaining kidney following partial or total ablation of a kidney are not well understood. This present study provides novel data characterizing the role of mitochondrial metabolism and oxidative stress in the phenomena of compensatory renal hypertrophy of a remnant kidney in the early 3‐day period following unilateral nephrectomy (UNX). The data indicate that mitochondria become the dominant source of increased reactive oxygen species (ROS) production following UNX and could represent an important hypertrophic signaling mechanism.